2010
DOI: 10.3201/eid1610.100374
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Drug Monitoring for Slow Response to Tuberculosis Treatment in a State Control Program, Virginia, USA

Abstract: TOC summary: Diabetes was associated with increased risk for slow response and low rifampin levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
115
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(121 citation statements)
references
References 27 publications
4
115
0
2
Order By: Relevance
“…A near inverse correlation was obtained in diabetic patients (Pearson's correlation=-0.402, P value=0.001); however such a correlation was not observed in non-diabetic pulmonary tuberculosis patients suggesting that the drug absorption is disfavoured only under hyperglycemic conditions and linear relationship does not exist between blood glucose and rifampicin Cmax (Pearson's correlation=0.006, P Value=0.962). This is similar to the study reported by Nijland et al (2006), Heysell et al (2010) and Heysell et al (2013) [12,[16][17]. The RBS vs Cmax correlation plot of non-diabetic and diabetic PTB patients is shown in fig.…”
Section: Fig 2: Distribution Based On Cat Regimensupporting
confidence: 80%
“…A near inverse correlation was obtained in diabetic patients (Pearson's correlation=-0.402, P value=0.001); however such a correlation was not observed in non-diabetic pulmonary tuberculosis patients suggesting that the drug absorption is disfavoured only under hyperglycemic conditions and linear relationship does not exist between blood glucose and rifampicin Cmax (Pearson's correlation=0.006, P Value=0.962). This is similar to the study reported by Nijland et al (2006), Heysell et al (2010) and Heysell et al (2013) [12,[16][17]. The RBS vs Cmax correlation plot of non-diabetic and diabetic PTB patients is shown in fig.…”
Section: Fig 2: Distribution Based On Cat Regimensupporting
confidence: 80%
“…TDM, although not yet popular among TB specialists, is well known in clinical pharmacology [20][21][22]. It is based on the collection of blood samples and allows the ex vivo evaluation of blood-drug concentration, and, consequently, of its potential quantitative effect on the pharmacological target.…”
mentioning
confidence: 99%
“…There are also reports that suggest that a higher dose of RMP is efficacious without serious adverse effects (25)(26)(27). A number of previous studies showed that low serum levels of INH and/or RMP could be problematic because they are associated with low therapeutic efficacy and relatively high therapeutic failure (28)(29)(30). Although limited data are available on dose and toxicity, physicians may be concerned that attempts to increase the dose of anti-TB drugs may lead to an increase in the frequency of anti-TB DIH.…”
Section: Discussionmentioning
confidence: 99%